2012
DOI: 10.1007/s11802-012-1802-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two major histocompatibility (MH) class II A genes and their association to Vibrio anguillarum infection in half-smooth tongue sole (Cynoglossus semilaevis)

Abstract: Major histocompatibility complex class II antigens are important in vertebrate immune system. In the present study, the full cDNA sequence of class II A gene was synthesized by RACE-PCR from half-smooth tongue sole (Cynoglossus semilaevis), and its open reading frame (ORF) polymorphism was studied. The whole cDNA sequence was 992 bp in length, including the ORF with 717 bp. Twenty-five alleles were identified and clustered into two distinct groups according to the specific nucleotides/ amino acids in specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…91, 92, 94, 95, 101 and 103) with gene‐unique amino acid in exon 2 (Figure a). Cyse‐DAA 's unique amino acids in those six sites are Asn 91 , Ser 92 , Ser 94 , Gly 95 , Lys 101 and Lys 103 , while Cyse‐DBA 's unique residues are Thr 91 , Val/Gly 92 , Gln/Glu 94 , Ala 95 , Leu 101 and Asn 103 (Figure a, Cyse‐DBA could be Thr/Ala/Lys/Ile 91 according to alleles isolated before (Li et al., )). Based on the PBRs of HLA‐DRA (Brown et al., ), the putative PBRs in tongue sole class II A are predicted and shown in Figure a, with most of the putative PBRs polymorphic.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…91, 92, 94, 95, 101 and 103) with gene‐unique amino acid in exon 2 (Figure a). Cyse‐DAA 's unique amino acids in those six sites are Asn 91 , Ser 92 , Ser 94 , Gly 95 , Lys 101 and Lys 103 , while Cyse‐DBA 's unique residues are Thr 91 , Val/Gly 92 , Gln/Glu 94 , Ala 95 , Leu 101 and Asn 103 (Figure a, Cyse‐DBA could be Thr/Ala/Lys/Ile 91 according to alleles isolated before (Li et al., )). Based on the PBRs of HLA‐DRA (Brown et al., ), the putative PBRs in tongue sole class II A are predicted and shown in Figure a, with most of the putative PBRs polymorphic.…”
Section: Resultsmentioning
confidence: 97%
“…Our previous study suggested that in tongue sole, MHC class II A may have been duplicated into two genes based on the ORF sequences, with most of the polymorphism existing in exons 2 and 3 (Li et al., ). In order to verify this, primers MIIA‐AbFw and MIIA‐AbRv, which could amplify a fragment of around 800 bp long, spanning complete exon 2, intron 2 and exon 3, were used to isolate alleles of class II A from the three families used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations